Integrated 68Ga-HBED-CC-PSMAPET/MRI in patients with suspected recurrent prostate cancer - Lütje, Susanne; Cohnen, Joseph; Gomez, Benedikt; Grüneisen, Johannes; Sawicki, Lino M.; Rübben, Herbert; Bockisch, Andreas; Umutlu, Lale; Pöppel, Thorsten D.; Wetter, Axel (Nuklearmedizin - NuclearMedicine, 2017)
Aim: To evaluate the diagnostic accuracy of FDG PET/CT in the detection of asymptomatic recurrence in patients with malignant melanoma who have had resection of their primary lesion. We also aimed to determine the pattern and factors predisposing to disease recurrence. Methods: Patients with malignant melanoma who have had surgical resection of their disease and without any clinical evidence of disease recurrence were followed- up with FDG PET/CT. The diagnostic accuracy of FDG PET/CT, pattern of recurrence and factors predictive of disease recurrence were determined. Results: A total of 144 patients were followed-up for a median period of 50.50 months. Asymptomatic recurrence was seen in 37 patients (25.7 %) with a median time to recurrence of 20 months. Lymph node was the commonest site of asymptomatic recurrence. Sex, tumour depth, histology type and presence of nodal metastasis were significant predictors of tumour recurrence. Age, race, site of primary lesion, type of lymph node resection were not significant predictors of disease recurrence. Race has a significant effect on the histological subtype of tumour (nodular maligna was more common in Caucasian while acral lentiginous was more prevalent in the Blacks) and the site of the primary lesion (lower limb in Blacks and trunk in Caucasians). Sensitivity, specificity and accuracy of FDG PET/CT for the detection of disease recurrence were 94.5 %, 87.6 % and 89.6 % respectively. Conclusion: FDG PET/CT is a suitable modality for early detection of asymptomatic recurrence of malignant melanoma. Asymptomatic recurrence most commonly occurs in lymph nodes. Sex, nodal metastasis and tumour pathologic features are predictors of recurrence.
Keywords: PSMA; prostate cancer; PET/MRI; PET/CT